2022
DOI: 10.5187/jast.2022.e83
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of male fertility using Ras-related proteins

Abstract: Jeong-Won Bae (https://orcid.org/0000-0002-7030-7767) Ju-Mi Hwang (https://orcid.org/0000-0003-1776-9759) Woo-Sung Kwon (https://orcid.org/0000-0002-0848-7189) Competing interestsNo potential conflict of interest relevant to this article was reported. Funding sourcesState funding sources (grants, funding sources, equipment, and supplies). Include name and number of grant if available.This study was conducted with the support of the Gyeongsangbukdo agricultural and fishery R&D activation project Authors' contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…These proteins are also recognized for their involvement in male fertility, contributing to the origin of the acrosome from the Golgi apparatus during spermatogenesis ( Moreno et al, 2000 ; Ramalho-Santos et al, 2001 ). Additionally, Rab proteins contribute to acrosome formation and reaction as well as sperm motility ( Bae et al, 2022a ). Specific Rab proteins, such as Rab8B, are associated with dynamic junctions in the testes ( Lau & Mruk, 2003 ), and Rab2A serves as a biomarker for boar fertility evaluation ( Kwon et al., 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These proteins are also recognized for their involvement in male fertility, contributing to the origin of the acrosome from the Golgi apparatus during spermatogenesis ( Moreno et al, 2000 ; Ramalho-Santos et al, 2001 ). Additionally, Rab proteins contribute to acrosome formation and reaction as well as sperm motility ( Bae et al, 2022a ). Specific Rab proteins, such as Rab8B, are associated with dynamic junctions in the testes ( Lau & Mruk, 2003 ), and Rab2A serves as a biomarker for boar fertility evaluation ( Kwon et al., 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Bae et al. demonstrated that various Rab proteins are present in the sperm head and tail, with several Rab proteins correlating with motion parameters ( Bae et al, 2019 , 2022a ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When using RAB2A in Yorkshire, noncapacitated spermatozoa were more efficient at predicting fertility but in the Duroc breed it was more predictive in capacitated spermatozoa. A follow-up study of spermatozoa from 31 Duroc boars measured Rab proteins before and after capacitation, correlating these to litter size (Bae et al, 2022).…”
Section: Such In Amentioning
confidence: 99%
“…When using RAB2A in Yorkshire, noncapacitated spermatozoa were more efficient at predicting fertility but in the Duroc breed it was more predictive in capacitated spermatozoa. A follow‐up study of spermatozoa from 31 Duroc boars measured Rab proteins before and after capacitation, correlating these to litter size (Bae et al, 2022). They found Rab3A, 4, 5, 8A, 9, and 25 abundance before capacitation and Rab3A, 4, 5, 8A, 9, and 14 after capacitation were negatively correlated with litter size.…”
Section: Capacitation Evaluation As a Predictor Of Boar Fertilitymentioning
confidence: 99%